2020
DOI: 10.20448/2002.81.21.29
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of International Financial Reporting Standards on the Association between Foreign Direct Investment and Economic Growth: Evidence from Selected Countries in Africa

Abstract: The study aims at examining how IFRS adoption influences the relationship existing among foreign direct investment (FDI) and economic growth. The data consist of 12 developing economies that are the highest recipients of FDI in Africa, and the years of study are from 1996-2018. Using Ordinary Least Square and Generalized Least Square method of estimation, the result shows that IFRS is significantly positive to FDI. With FDI inflows in these countries, the result provides evidence that Non fully-IFRS adopted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this study, the independent variable of interest is IFRS adoption (IFRSadopt), a dummy variable that takes values of 0 and 1, where the values indicate the presence or absence of a variable (Gordon et al. , 2012; Ugwu and Okoye, 2018; Gu and Prah, 2020). Adoption is expressed as the full adoption and use of IFRS standards by domestic listed companies in a jurisdiction that has adopted IFRS.…”
Section: Methodology and Datamentioning
confidence: 99%
“…In this study, the independent variable of interest is IFRS adoption (IFRSadopt), a dummy variable that takes values of 0 and 1, where the values indicate the presence or absence of a variable (Gordon et al. , 2012; Ugwu and Okoye, 2018; Gu and Prah, 2020). Adoption is expressed as the full adoption and use of IFRS standards by domestic listed companies in a jurisdiction that has adopted IFRS.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Like all these other related variables, the product also means the quality of products has a major effect on exporting the product. Good quality products increase the export otherwise decrease in exports (Fan, Hossain, Islam, & Yahia, 2019;Girangwa, Rono, & Mose, 2020;Gö ral, 2020;Gu & Prah, 2020;Papadas, Avlonitis, & Carrigan, 2017). Figure 2 showed that the theoretical link between the marketing performance determinants and durian product exporting with the mediation of motivation to export and Attitude towards exporting.…”
Section: Introductionmentioning
confidence: 92%
“…To most people, job loss will reduce current living standards, and concerns for the future that will decrease people's income (Mankiw, 2018). Further, investment is basically economic development activities that can be carried out by both private and public parties, which aim to increase economic growth and, in the long run, can improve the people's living standards (Afonso & Aubyn, 2019;Firmansyah & Nasih, 2019;Gilbert & François, 2020;Gu & Prah, 2020;Hanif, Faraz Raza, Gago-de-Santos, & Abbas, 2019;Pradhan, Arvin, & Hall, 2019;O. P. Shukla, 2020;Udemba, Magazzino, & Bekun, 2020).…”
Section: Introductionmentioning
confidence: 99%